Clinical activity of azacitidine in patients who relapse after allogeneic stem cell transplantation for acute myeloid leukemia - Craddock, Charles; Labopin, Myriam; Robin, Marie; Finke, Juergen; Chevallier, Patrice; Yakoub-Agha, Ibrahim; Bourhis, Jean Henri; Sengelov, Henrik; Blaise, Didier; Luft, Thomas; Hallek, Michael; Kröger, Nicolaus; et al. (Haematologica, 2016)
Disease relapse is the most common cause of treatment failure after allogeneic stem cell transplantation for acute myeloid leukemia and myelodysplastic syndromes, yet treatment options for such patients remain extremely limited. Azacitidine is an important new therapy in high-risk myelodysplastic syndromes and acute myeloid leukemia but its role in patients who relapse post allograft has not been defined. We studied the tolerability and activity of azacitidine in 181 patients who relapsed after an allograft for acute myeloid leukemia (n=116) or myelodysplastic syndromes (n=65). Sixty-nine patients received additional donor lymphocyte infusions. Forty-six of 157 (25%) assessable patients responded to azacitidine therapy: 24 (15%) achieved a complete remission and 22 a partial remission. Response rates were higher in patients transplanted in complete remission (P=0.04) and those transplanted for myelodysplastic syndromes (P=0.023). In patients who achieved a complete remission, the 2-year overall survival was 48% versus 12% for the whole population. Overall survival was determined by time to relapse post transplant more than six months (P=0.001) and percentage of blasts in the bone marrow at time of relapse (P=0.01). The concurrent administration of donor lymphocyte infusion did not improve either response rates or overall survival in patients treated with azacitidine. An azacitidine relapse prognostic score was developed which predicted 2-year overall survival ranging from 3%-37% (P=0.00001). We conclude that azacitidine represents an important new therapy in selected patients with acute myeloid leukemia/myelodysplastic syndromes who relapse after allogeneic stem cell transplantation. Prospective studies to confirm optimal treatment options in this challenging patient population are required.
Gesehen am 05.05.2020